Total Quality Management System in an Education Environment: The Case of a Private University in Bahrain - Akbar, Mahmood A.; Ali, Mohd H.; Alam, Syed S. (Journal of Reviews on Global Economics, 2019)
The study aims to analyze and explain the effectiveness and efficiency of implementing total quality management principles in private educational institutions. The context of the study narrowed down the areas of comparisons to tutorial conducts, student affairs and infrastructure. A detailed analysis of the existing total quality management currently in place at the selected university was duly comprehended. This resulted in finding the flaws/weaknesses in the system of universities in the kingdom of Bahrain generally. Findings through a survey and interview sessions indicated that teachers were not consulted for any changes in curriculum which leads to a lack of co-operation between management and teachers. Another problem in regards to the total quality management implementation was that students perceived the university as not being concerned with maintenance of the premises. Moreover, student affairs/services section was seriously lacking sport facilities, limited training sessions, poor equipment maintenance.